Redistributive populism versus strengthening property rights: A comparative study of Venezuela and Zimbabwe, and Uruguay and Botswana - van Zyl, Ernst Jacobus (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.